2020
DOI: 10.1021/jacs.0c08179
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Double Helices from Small C3-Symmetrical Molecules Aggregated in Water

Abstract: Supramolecular fibers in water, micrometers long and several nanometers in width, are among the most studied nanostructures for biomedical applications. These supramolecular polymers are formed through a spontaneous self-assembly process of small amphiphilic molecules by specific secondary interactions. Although many compounds do not possess a stereocenter, recent studies suggest the (co)existence of helical structures, albeit in racemic form. Here, we disclose a series of supramolecular (co)polymers based on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 55 publications
1
46
0
Order By: Relevance
“…Recently, we found that double helices are present in the sample next to other supramolecular structures. 47 We hypothesize that the formation of a double helix stabilizes the interactions between the BTAs, which would prevent them from moving into the solvent and therefore a slowing down of the H/D exchange of the core amides can occur.…”
Section: Consequences Of the Mechanism Of Exchange On The Hdx Dynamics In Supramolecular Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we found that double helices are present in the sample next to other supramolecular structures. 47 We hypothesize that the formation of a double helix stabilizes the interactions between the BTAs, which would prevent them from moving into the solvent and therefore a slowing down of the H/D exchange of the core amides can occur.…”
Section: Consequences Of the Mechanism Of Exchange On The Hdx Dynamics In Supramolecular Polymersmentioning
confidence: 99%
“…We recently elucidated that BTA (1) forms a double helical structure in water. 47 In contrast, diacetylene bis-urea amphiphile (BU [2]) forms fibrous bundles, 48 and the two benzotrithiophenes (BTT-5F [3] and BTT [4]) form single fibers (Scheme 1). 13 BTT-5F (3) polymerizes via an isodesmic mechanism, whereas all other monomers polymerize via a cooperative mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that, upon closer examination, at least some nanofibers in aqueous solutions comprise two smaller fibers, either twisted or parallel. 28,29 Furthermore, several studies have reported the formation of more complicated structures (e.g., nanoribbons or triple helices) during the self-assembly of BTAbased molecules in organic solvents or their mixtures with water. [30][31][32] In water, stepwise self-assembly into clearly defined double helical nanorods was reported only for BTA-based Aucontaining metalloamphiphiles.…”
Section: Introductionmentioning
confidence: 99%
“…96 Very recently, Meijer, Böttcher, and coworkers utilized cryo-TEM with advanced cryo-electron tomography analysis to study details of the structure of another supramolecular polymer in water. 157 In this analysis method, multiple views from different directions…”
Section: Microscopy Techniquesmentioning
confidence: 99%
“…158 However, employing the cryo-electron tomography analysis they realized that these units can form micrometer-long, double helix structures with a pitch size that is tunable by the choice of the tail compositions. 157 Another microscopy technique that is widely used for studying supramolecular polymer materials is fluorescence microscopy including confocal microscopy and high-resolution fluorescence microscopy such as stochastic optical reconstruction microscopy (STORM). 159 Hamachi and coworkers studied the self-assembly of peptide-based and lipid-like gelators into nanofibers and further the self-sorting of these nanofibers by in situ imaging of a confocal microscope.…”
Section: Reviewmentioning
confidence: 99%